BELANJA PENDIDIKAN, KESEHATAN, DAN PERLINDUNGAN SOSIAL DALAM PENANGGULANGAN KEMISKINAN: BUKTI EMPIRIS DARI SULAWESI TENGGARA - Asrianti Dja'wa; Tajuddin Tajuddin; Surianti Surianti; Darmanto Darmanto; Rudi Abdullah (JISEF : Journal Of International Sharia Economics And Financial, 2026)
This study examines the effects of local government expenditure on health, education, and social protection on poverty across 17 districts and municipalities in Southeast Sulawesi, Indonesia, during 2018-2022. Secondary data from Statistics Indonesia and the Directorate General of Fiscal Balance form a balanced panel of 85 observations. Panel regression is estimated after Chow, Hausman, and Lagrange Multiplier specification tests, which support a Random Effects Model. Health expenditure has a negative but statistically insignificant coefficient, whereas education and social protection expenditures have negative and significant coefficients at the 5 percent level. Jointly, the three expenditure categories significantly explain poverty variation, although the model's explanatory power remains modest. The findings indicate that fiscal effectiveness depends not only on budget size but also on expenditure composition, targeting accuracy, equitable access, and implementation quality. Policy should prioritize outcome-oriented education spending, well-targeted social protection, and equitable health services that strengthen financial protection for poor households.